Marriage Exemptions for Minors in Sidoarjo Regency in 2026 - Ely Widi Astutik (Publikasi Indonesia, 2026)
This study examines the phenomenon of marriage dispensation for minors in Sidoarjo Regency in 2026 and analyzes the factors contributing to the increase in applications for underage marriage dispensation. Although the government has amended the minimum age requirement for marriage through Law Number 16 of 2019, applications for marriage dispensation continue to increase in several regions, including Sidoarjo Regency. This research aims to analyze the implementation of marriage dispensation policies, the factors influencing underage marriage, and the role of government institutions in preventing child marriage. The study uses a qualitative juridical-sociological approach by examining legislation, court data, and interviews with officials from the Religious Court and the Women and Child Protection Office in Sidoarjo Regency. The results show that economic conditions, low educational attainment, cultural pressure, pregnancy outside marriage, and limited public awareness are the dominant factors contributing to underage marriage. In practice, the marriage dispensation mechanism is frequently used as a legal pathway to bypass the minimum marriage age requirement. The study also finds that collaboration among the government, Religious Courts, educational institutions, and community organizations is essential to reducing child marriage rates. Therefore, strengthening supervision, public education, and stricter implementation of marriage dispensation regulations are necessary to ensure better protection of children’s rights.